2020
DOI: 10.1088/1361-6595/ab56dc
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of helicon plasma by local OES

Abstract: Optical emission spectroscopy (OES) is a common method for characterizing radio frequency (RF) discharge plasmas. Particulary, helicon plasma is featured by its high plasma density among all RF-excited plasmas. In order to obtain the spatial-resolved information of a helicon plasma, local optical emission spectroscopy (LOES) with a 3 mm spatial resolution was proposed and carried out to evaluate the local electron density and temperature. The plasma emission intensity via LOES was measured and compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…The efficiency of ionization was promoted accordingly. This characteristic of mode transition was reported previously by our group [30–32] as well as the others [34–36].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The efficiency of ionization was promoted accordingly. This characteristic of mode transition was reported previously by our group [30–32] as well as the others [34–36].…”
Section: Resultssupporting
confidence: 87%
“…Since 811.53 nm emission from the transition 3p 5 the DL on axis. Besides, the intensity of 811.53 nm line can be converted to the electron density by certain relations [31,32]. Hence the corresponding electron density is also displayed here in Figure 3b.…”
Section: Experiments and Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Ruilin Cui talked about the experimental results of discharge characteristics and heating mechanism of argon helicon plasma in different wave modes from Langmuir probe, magnetic probe, and local optical emission spectroscopy (LOES) [40]. It is shown that there exist three or four distinct wave modes (i.e., number of half-wavelengths along the axial direction m z 1, 3, 5, or 7) under different operating conditions.…”
Section: Introductionmentioning
confidence: 99%